Interrogating Assessment in the Age of Generative AI - Margaret Blackie; Sioux McKenna; Neil Kramm; Nicola Pallitt (African Journal of Inter-Multidisciplinary Studies)
Generative AI (GenAI) has foregrounded important educational issues. In this conceptual paper we build on Blackie’s work on knowledge-building and assessment practices to argue that responding to GenAI in educationally sound and sustainable ways requires engagement with the purpose of a higher education. A university education should transform students’ understanding of the world, themselves, and their relationship to the world in discipline-specific ways. We need to understand what it means to be gain expertise in a field before we can consider what it means to assess competence in that field. In this article, we draw on the discipline of Chemistry to reflect on the nature of the target knowledge and knowing and how this then aligns to the approach to assessment. It is only then that we can consider how GenAI might positively or negatively affect the development and demonstration of competence. In addition, because education is inherently relational, we also have to endeavour to nurture and assess such competence on a consciously created foundation of trust.